The effect of group therapy on anxiety level of nursing students in Psychiatry ward - Narges Rahmani; Kolsoum akbarnatajbishe; Azadeh kiapour; Hosein Alipour (مجله ایرانی آموزش در علوم پزشکی, 2019)
Introduction: Nurses have stressful attitudes towards psychiatric patients who play significant role in their care. This study endeavored to determine the effect of group therapy on the anxiety of nursing students in psychiatric ward of Babol Yahyanejad hospital. Methods: In this quasi-experimental study sample consisted of 36 nursing students of the fifth semester at Babol Islamic Azad university who were randomly assigned to two experimental and control groups. The experimental group participated for six sessions of group therapy while the control group passed training sessions, they did not attend these sessions. The survey instrument included demographic characteristics, Spielbergerr Anxiety Inventory. Data were analyzed through covariance test. Results: The majority of the samples, 11 students (61.1%) had moderate to low anxiety in the experimental and control groups before the treatment group, while the majority of the samples (61.1%) in the experimental group after the group therapy received mild anxiety. According to the results of the covariance analysis, the two groups after the test significantly (p <0.05) were different in terms of anxiety level. Conclusion: These results indicated the effectiveness of group therapy in reducing anxiety of students in the Psychiatry ward. According to the results holding training classes on how to deal with Patients and systematic interview process before attending in psychiatric wards is recommended.